Na fronteira da exclusão: ações de enfrentamento à violência na juventude - Souza, Candida de (Universidade Federal do Rio Grande do Norte, 2012)
In present day society, violence, mainly in urban centers, has emerged as one of the main consequences of the “social question”, having great impact on many people's lives, especially the young ones.Therefore, the government has been called to act in preventing and combating this form of rights violation. The situation in Natal/RN corroborates national rates concerning the incidence of violence in youth, and reveals alarming data, specifically in its suburbs.It was decided to define the field of research in the district Felipe Camarão, given the historical high homicide rate against its young population. The aim of this study was to identify and to examine initiatives focused on prevention and combating against youth violence that are being developed in Felipe Camarão, in what basis they have been developed and how they translate into action. More specifically, it aimed to achieve a survey and characterization of the institutions that have actions focused on the young people in Felipe Camarão, as well as to analyze the professionals' starting point for the implementation and coordination of actions in the process of violence reduction, identifying what they do and how they do it. Ten institutions were identified as having their full or partial actions focused on the young population. It has been conducted focal groups with professionals from all institutions. Data were analyzed from the perspective of historical and dialectical method, based on the Método Comparativo Constante (Grounded Theory). The results were presented from three analysis lines: the conceptions of professionals on violence; the initiatives towards violence prevention in Felipe Camarão; and the challenges and perspectives found in the violence reduction process. We point out that the phenomenon of violence presents itself as commonplace in people's lives, which contributes to strengthening a culture of fear, as well as stigmatization of a neighborhood, whether in media or in social imaginary. Actions aimed to young people need to be better structured, articulated and to have a critical perspective on the process of violence prevention, in addition to greater territorial coverage. We argue that the implementation of actions with emancipatory nature, especially to young population, allowing them to build new projects for life, associated to a strengthening of state action in the preventive scope, through policies for high quality education access and dignified work opportunities, in addition to the consolidation of an effective social capital, are important factors in the process of violence reduction in Felipe Camarão.
Keywords: Direitos humanos; Juventude; Violência; CNPQ::CIENCIAS HUMANAS::PSICOLOGIA